1997
DOI: 10.1080/00288330.1997.9516793
|View full text |Cite
|
Sign up to set email alerts
|

Land‐use effects on the hyporheic ecology of five small streams near Hamilton, New Zealand

Abstract: Although the importance of the subsurface saturated interstitial zone (hyporheic zone) to the ecological functioning and maintenance of water quality of stream ecosystems is well known, there is little information on the impacts of different forms of land use upon this zone. Hyporheic physico-chemistry and invertebrates were compared among small streams draining hillcountry catchments under pasture, exotic pine forest, and native forest near Hamilton, New Zealand. In streams draining native forest, the hyporhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
76
2
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 30 publications
2
76
2
2
Order By: Relevance
“…After forest clearance the hyporheic zone occurring under the gravel bars that were originally exposed at low flows is mainly covered in fine sediment built into new stream banks. Boulton et al (1997) have suggested that this process reduces the exchange of surface water with the underlying hyporheic zone so that it is no longer suitable habitat for hyporheic fauna owing, particularly, to low dissolved oxygen. The remaining hyporheic habitat, under the reduced streambed area in narrow pasture streams, appears also to have been degraded by sediment clogging and reduced interstitial dissolved oxygen (Boulton et al 1997).…”
mentioning
confidence: 99%
“…After forest clearance the hyporheic zone occurring under the gravel bars that were originally exposed at low flows is mainly covered in fine sediment built into new stream banks. Boulton et al (1997) have suggested that this process reduces the exchange of surface water with the underlying hyporheic zone so that it is no longer suitable habitat for hyporheic fauna owing, particularly, to low dissolved oxygen. The remaining hyporheic habitat, under the reduced streambed area in narrow pasture streams, appears also to have been degraded by sediment clogging and reduced interstitial dissolved oxygen (Boulton et al 1997).…”
mentioning
confidence: 99%
“…BOU, 1977 ;RICHARDS et BACON, 1994 ;BOULTON et al, 1997) permettant de cerner les effets du colmatage de la zone hyporhéique sur sa faune. La zone hyporhéique constitue pourtant un compartiment essentiel dans le fonctionnement des systèmes aquatiques en raison de la diversité et de l'abondance de sa faune ainsi que de son rôle dans la dynamique du système (BRUNKE et GONSER, 1997 ;WARD et al, 1998).…”
Section: Influence De L'infiltration Des Sédiments Fins Sur L'hyporhéosunclassified
“…Plusieurs auteurs (MARIDET et al, 1992 ;RICHARDS et BACON, 1994 ;MARIDET et al, 1996) ont constaté à l'échelle du micro-habitat, la réduction de l'abondance et du nombre de taxons en relation avec la réduction de la porosité ou l'augmentation de la proportion de sédiments fins. Parmi la faune hyporhéique, ce sont principalement les organismes benthiques qui sont affectés par le colmatage tandis que de nombreux taxons strictement hypogés semblent se satisfaire de concentrations en oxygène plus réduites (BOULTON et al, 1997 ;MALARD et HERVANT, 1999). Compte tenu de l'importance de la zone hyporhéique dans le fonctionnement du système (e.g.…”
Section: Influence De L'infiltration Des Sédiments Fins Sur L'hyporhéosunclassified
“…The effects of the high benthic sedimentation in pasture and pine forest (Quinn et al 1997a) on the hyporheic habitat and fauna were the focus of a paper by Boulton et al (1997). Their study indicated that a change from native forest to pasture land use reduces the quantity and quality of hyporheic habitat and alters the composition and diversity of hyporheic fauna.…”
Section: Overview Of Special Issue Papersmentioning
confidence: 99%
“…The studies use a variety of approaches to determining the influence of land use on stream ecosystems. Six papers in this issue (Boulton et al 1997;Davies-Colley 1997;Hicks 1997;Hicks & McCaughan 1997;Quinn et al 1997a) use the "natural experiment" provided by the streams draining Hakarimata Range catchments, with similar geology, topography, rainfall, and soils, to investigate land-use effects. This involves substituting space for time and comparing replicated sites in each land use.…”
Section: Overview Of Special Issue Papersmentioning
confidence: 99%